IMPLEMENTATION OF WASTEWATER POLLUTION CONTROL IN THE FISH PROCESSING INDUSTRY, KEDUNGREJO VILLAGE, MUNCAR DISTRICT BANYUWANGI REGENCY - Sri Wilujeng; Sutrisno Sutrisno; Musta'ana Musta'ana (Jurnal Ekonomi, 2022)
The existence of large fish processing industries in Kedungrejo Village, Muncar Subdistrict, have mostly developed using modern technology, which has had a lot of impact on the environment, because most of the Wastewater Treatment Plants (WWTPs) are not functioning properly, and the waste water that is discharged is not functioning properly. meet water quality standards, some are even discharged directly into the waters without being processed or recycled. Based on Banyuwangi Regency Regional Regulation Number 13 of 2017 concerning Water Pollution Control, the Regional Government is obliged to protect and manage the environment so that the implementation of development can be sustainable. The environmental management policy in Banyuwangi Regency is implemented by the Banyuwangi Regency Environmental Service (DLH). The aim of the study was to determine the implementation of waste water pollution control in the fish processing industry in Kedungrejo Village, Muncar District, Banyuwangi Regency. The method used in this study, namely: descriptive qualitative based on the principles of William N. Dunn. The results of this study prove that there are still violations committed by fish processing industry owners in disposing of their waste water. The existence of waste water pollution from the fish processing industry has been proven to pollute the Kalimati River in Kedungrejo Village, Muncar District, Banyuwangi Regency. The lack of attention from all parties to implement local government policies regarding Banyuwangi Regency Regional Regulation Number 13 of 2017 concerning Waste Water Pollution Control in the fish processing industry is a factor causing Muncar waters to date are still experiencing water pollution, especially in Kedungrejo Village, Muncar District, Banyuwangi Regency.